The Changing Nature of Health Professionals' Work: The Impact of Infectious Disease - Kaba, Alyshah (My University, 2011)
Background. As disease patterns change, healthcare facilities have had to adapt and create new strategies. Little is known about the impact of infectious disease on the changing nature of work for frontline nurses, healthcare executives laboratory staff, and infection control practitioners (ICPs), in these disciplines in community hospitals. In the past seven years, there has been an increase in the incidence of infectious disease in Ontario (MRSA, VRE, C. difficile). As a result, there has been implementation of new infection control policies and practices, and transparency in the public reporting systems (Ministry of Health and Long-Term Care [MOHLTC], 2008). However, no research has focused on how these changes have impacted the work of health professionals.
Purpose. The purpose of this study is to explore the impact of hospital-acquired infections (HAIs) on the changing nature of work of frontline nurses, healthcare executives, laboratory staff, and infection control practitioners. Methods. The study uses an exploratory descriptive case study design and is situated in South Eastern Ontario (Niagara Health System). The methodology includes document analysis, demographic workforce questionnaires, and semi-structured interviews.
Findings. The findings demonstrate that work has changed for all health professionals because of (1) the continued increase in infectious diseases, (2) the proliferation of infection control policies and practices, (3) the increase in data management and data-based decisions, and (4) increased communication and connectivity required across disciplines.
Conclusion. Implications for future research include the need to address streamlining changes at the healthcare system, institutional, and clinical level. There needs to be an evaluation of the evidence supporting existing institutional policies and procedures, and of the care structures in the management of infectious diseases.
Keywords: infectious disease; hospital work; nurses; laboratory staff; infection control practitioners; executives; Medicine and Health Sciences; Medicine and Health Sciences